Large Individual-Level Variability in Diel Activity and Depth Use for the Common Lionfish (Pterois miles) - Gavriel, Tal; Pickholtz, Renanel; Belmaker, Jonathan (Frontiers in Marine Science, 2021)
The common lionfish, Pterois miles, a notoriously invasive species known for its harmful effect on native fish communities in the Atlantic Ocean, has recently begun spreading across the Mediterranean Sea. The wide niche breadth of the lionfish has been hypothesized to facilitate its invasion success. However, it is unclear to what extent this wide niche-breadth is associated with individual-level variation and repeatable behavior over time. Large individual-level behavioral variations may allow individuals to adapt quickly to local conditions, increasing the species’ chance of invasion success and complicating mitigation efforts. In this study, we used an acoustic telemetry system in P. miles’ native Red Sea environment to explore individual-level variation in depth preference and diel activity. A wide depth range may indicate an ability to tolerate a variety of biotic and abiotic conditions, and variability in diel activity may indicate an ability to exploit multiple diet sources. We found large individual-level variability in P. miles’ activity hours; although all tracked fish were active during both sunrise and sunset, certain individuals had prolonged activity hours to variable extents. Moreover, individuals often change their patterns over time, showing low repeatability. We also found that individuals had different depth preferences and commuted between shallow and deep waters over short periods of time. This study is one of the first to explore diel activity as an individual-level trait in wild fish. The variability found in depth and diel activity is likely one of the reasons P. miles has been so successful in invading the Mediterranean Sea. In addition, this variability may impact mitigation efforts within the Mediterranean Sea as nocturnal individuals from deeper waters might replenish diurnally culled shallow-water populations.